2020
DOI: 10.33102/sainsinsani.vol5no1.189
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Aggression, Self-esteem and Cyberbullying among Undergraduates in Malaysia

Abstract: The prevalence of cyberbullying cases has been increasing over the years and it causes detrimental effects on one's mental health and psychological well-being. This cross-sectional research aims to determine the significant relationship between proactive aggression, reactive aggression and self-esteem on cyberbullying among undergraduates in Malaysia. 255 participants were recruited through purposive sampling. Questionnaires were distributed online via social media platforms such as Facebook, Instagram, WhatsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The literature review provides valuable insights into the complex interplay between selfesteem, aggression, cyberbullying, and the influence of video games on these variables. Lokithasan et al (2020) conducted a survey among vocational high school students and found a negative correlation between empathy and cyberbullying, suggesting that individuals with higher levels of empathy were less likely to engage in online aggressive behavior. Conversely, a positive correlation was found between self-esteem and cyberbullying, indicating that individuals with higher self-esteem may be more prone to perpetrating harmful acts online.…”
Section: Self-esteem and Aggressionmentioning
confidence: 99%
“…The literature review provides valuable insights into the complex interplay between selfesteem, aggression, cyberbullying, and the influence of video games on these variables. Lokithasan et al (2020) conducted a survey among vocational high school students and found a negative correlation between empathy and cyberbullying, suggesting that individuals with higher levels of empathy were less likely to engage in online aggressive behavior. Conversely, a positive correlation was found between self-esteem and cyberbullying, indicating that individuals with higher self-esteem may be more prone to perpetrating harmful acts online.…”
Section: Self-esteem and Aggressionmentioning
confidence: 99%